Submaximal neuromuscular economy is related to cardiorespiratory fitness in endurance-trained runners - McCormack, W. P.; Yoo, C. J.; Harpstrite, K. M.; Shoepe, T. C.; Jennings, C. A.; Capel, L. M.; Copley, C. E.; McCormack, W. P. (Journal of Electromyography and Kinesiology, 2019)
A number of factors determine neuromuscular economy (NE) and running economy (RE) in endurance-trained runners. The purpose of this investigation was to examine the relationship between aerobic fitness and NE in endurance-trained runners. Twenty-seven endurance-trained runners (25.1 ± 10.2 y) completed a maximal voluntary isometric contraction of the leg extensors to measure maximal electromyography (EMGmax) amplitude of the vastus lateralis (VL) and rectus femoris (RF), a steady-state treadmill run at 9.66, 11.27, and 12.87 km·hr-1 and a maximal graded exercise test. Participants were outfitted with surface electrodes over the VL and RF muscles to record EMG amplitude throughout each test. During the steady-state test, the EMG (as a percentage of EMGmax) and oxygen consumption (VO2) over the final minute of each stage were established and considered NE and RE, respectively. Pearson product moment correlations were used to determine the relationships between VO2max and velocity at VO2max (vVO2max) and NE and RE. The results revealed significant negative correlations between VO2max and vVO2max and relative NE and RE at all three speeds. In addition, there were significant correlations between relative RE and NE at all three speeds. These results indicate that faster runners have improved NE and RE when expressed as a relative measure.